Comparison of analgesic efficacy of topical tramadol versus topical lidocaine in the control of postoperative pain in children after tonsillectomy: A randomized double-blinded clinical trial - Abdelwahab A. Saleh; Abdelfattah M. Abdelfattah (Wolters Kluwer Medknow Publications, 2023)
Background and aim Tonsillectomy is considered one of the most frequent minor surgeries conducted on a day-case basis on children, and usually associate with pain and sore throat. This study aimed to compare the effect peritonsillor tramadol and lidocaine in pain alleviation after tonsillectomy in pediatrics. Patients and methods This prospective, randomized, double blind, controlled clinical study included 80 children, aged 4-15 years. They were distributed into two groups; Group T (n=40) patients received swabs soaked with tramadol 5% diluted with saline 0.9% up to 10 ml; group L (n=40) patients received swabs soaked with ledocaine 2% 2 mg/kg diluted with saline 0.9% up to 10 ml. Post operative pain scores, bleeding, nausea, vomiting, sore throat, otalgia, fever, halitosis, and trismus were recorded. Results Pain score was significantly reduced in the lidocaine arm within two hours after surgery, compared to the tramadol arm (P<0.05). The mean modified VAS score at day 7 was significantly reduced in the tramadol arm, compared to lidocaine arm (1.21 Vs 2.42, P<0.05). No significant difference between the two arms was reported, in terms of postoperative nausea and vomiting, halitosis, fever and otalgia. More serious complications like post-tonsillectomy bleeding or trismus were not reported in either groups Conclusion Topical 5% tramadole and lidocaine has a significant value in post tonsillectomy analgesic effect. Lidocaine had rapid onset at 15 min and duration prolonged up to 2 hours. Tramadol had delayed onset and prolonged duration from 4 hr up to 7 days.